1999
DOI: 10.1080/00049158.1999.10674756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial stocking on stand development in even-aged mixed eucalypt regrowth: a preliminary model

Abstract: Even-aged, mixed species eucalypt regeneration with a wide range of initial stockings was established on a Tasmanian moist sclerophyll site by using a range of sowing rates. Stocking, growth and development were monitored on permanent measurement plots from the time of regeneration to age 16. Initial stocking data were combined with volume data from the age 13 and 16 measurements and used in conjunction with local expert knowledge on stand development to produce a preliminary model which predicts how initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Sites with different levels of initial conditions should also undergo succession at different rates (Martínez‐Ramos & García‐Orth, ; Martínez‐Ramos et al, ; Pickett & Cadenasso, ; Watt, ). For example, young sites with higher basal area tend to accumulate biomass at a faster rate compared to sites of similar age but with lower basal area (Babst, Bouriaud, Alexander, Trouet, & Frank, ; Lockett & Goodwin, ). Moreover, initial conditions in terms of forest canopy cover (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Sites with different levels of initial conditions should also undergo succession at different rates (Martínez‐Ramos & García‐Orth, ; Martínez‐Ramos et al, ; Pickett & Cadenasso, ; Watt, ). For example, young sites with higher basal area tend to accumulate biomass at a faster rate compared to sites of similar age but with lower basal area (Babst, Bouriaud, Alexander, Trouet, & Frank, ; Lockett & Goodwin, ). Moreover, initial conditions in terms of forest canopy cover (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The range of heterogeneity factors of l-21 (Table 5) is higher than that reported in the few stand map studies in eucalypt forests. Results from stand maps in artificially-sown mixed-species eucalypt forest in Tasmania had heterogeneity factors of l-14 (Lockett and Goodwin 1999). Hamilton (1984) showed that artificially sown E. regnans-E. delegatensis regeneration in the Central Highlands of Victoria had heterogeneity factors in the range of l-8 (calculated from Hamilton's data).…”
Section: All Species a Species Bmentioning
confidence: 96%
“…At the start of the project the only examples in Australian native forests were those from a 1-y-old dry mixed-species eucalypt forest in Tasmania (Lockett and Goodwin 1999), and some 4-y-old Eucalyptus regnans-E. delegatensis stands in the Central Highlands of Victoria (Hamilton 1984). Thus there was a need to prepare, for regeneration assessment, stand maps of seedling distribution over the range of forest types and silvicultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of stand development past the stage for which reliable stand data is available indicates that the current standards should produce acceptable timber production outcomes (Lockett and Goodwin 1998;Hamilton 1989), but those analyses do not take into account the effect of initial spatial pattern on tree form.…”
Section: Stocking By Quadrat (Fraction (%) Of 4 M 2 and 16 M 2 Plots mentioning
confidence: 99%
“…The resulting spatial variation in density is likely to have an influence on stand yield and self-thinning rate (Opie et a/. 1984;Lockett and Goodwin 1998). While stands may have sufficient seedlings per hectare, there may be areas where seedling density is below that required to maintain site productivity and good tree form.…”
Section: Introductionmentioning
confidence: 98%